Conductance and Solvation Behavior of Some Onium Dichromates in Aqueous-Ethanol Mixtures (Global Journal of Science Frontier Research, 2012)
The paper explores solvation behaviour of Nicotinium, Pyridinium and Quinolinium dichromates at 283K – 313K in ethanol, water and varying compositions (v/v) of water-ethanol mixtures. Analysis of conductance data to obtain Λo is on the lines of Kraus-Bray and Shedlovsky equations. Λo, the limiting molar ,varies with the composition of the solvent mixture. This is used in the interpretation of the preferential / discriminating solvation of cations by ethanol. The influence of mixed solvent composition on the solvation of ions is discussed in tune with the composition dependence of Walden product. The influence of the mixed solvent composition on the solvation of ions has been discussed with the help of ‘R’-factor.
Keywords: ion-pair association constant / ion-pair dissociation constant / solvation number / Rfactor/ limiting molar conductance/ thermodynamic parameter